(untitled) (Acta Judicial Journal, 2021)
The study of this topic is mainly due to the state of alert in which society is today as a consequence of the different cases that we are hearing about gender violence, which go beyond what was traditionally known as such. And that is because Internet is a tool in full expansion within the reach of any individual, which makes its more intensified use along with that of utilities such as social networks or applications such as those of instant messaging services or geolocation, is promoting the appearance of behaviors related to gender violence, which until then had gone unnoticed or did not know how to deal with it. And not only that, but the possibility of incorporating these communications as evidence in these criminal proceedings is a novel aspect in which there are no unanimous opinions due to the problems that this entails: mainly about their probative value and the need or not for expert evidence on them.